Field Efficacy of Selected Insecticides against Fall Armyworm, Spodoptera frugiperda (J.E. Smith) in Maize - Bajracharya, A.S.R.; Bhat, B.; Sharma, P. (Journal of the Plant Protection Society, 2020)
Abstract availalble with the full text.